Correlation between body image satisfaction, sports performance satisfaction, and score allocation of collegiate female UAAP Poomsae athletes - Iglesia, Aliana Denise D. 2000-
Poomsae is a non-combat competitive sport under one of the categories of Taekwondo Korean martial art combining hand and foot movement. When punches, blockings, and kicks are combined, a form is created. Performing different Poomsae forms is aesthetically judged beholding its impact and presence of elegance. While females place more body significance than males, it provides aesthetic experience when performing Poomsae which affects the athlete’s performance. In this study, a correlational research design was used to investigate the relationship between body image satisfaction and sports performance satisfaction to determine if neither has possible related effects that impact female athletes’ satisfaction and within the competition score aspect. The researcher gathered the actual scores of the female participants (n= 17) in the UAAP Season 86 under individual, mixed pair, and team events from elimination to final round performance and conducted online post-competition questionnaires in a 5-point Likert scale to assess how satisfied the participants on their body image and sports performance. Using Spearman’s correlation coefficient, the results found that there is a significant correlation between (1) body image satisfaction and sports performance satisfaction and (2) sports performance satisfaction and competition scores. However, an insignificant correlation was found between (3) body image satisfaction and competition scores.